Successful engraftment of epithelial cells derived from autologous rabbit buccal mucosal tissue, encapsulated in a polymer scaffold in a rabbit model of a urethral stricture, transplanted using the transurethral approach - Horiguchi, Akio; Ojima, Kenichiro; Shinchi, Masayuki; Kushibiki, Toshihiro; Mayumi, Yoshine; Miyai, Kosuke; Katoh, Shojiro; Takeda, Masayuki; Iwasaki, Masaru; Prakash, Vaddi Surya; Balamurugan, Madasamy; Rajmohan, Mathaiyan; et al. (Regenerative Therapy, 2021)
A pilot study reported an autologous buccal mucosal cell transplant in humans through the trans-urethral route using the buccal epithelium expanded and encapsulated in scaffold—hybrid approach to urethral stricture (BEES-HAUS), a minimally invasive approach to treat urethral stricture. Although successful outcomes were achieved in that study, for further validation, it is essential to prove that the transplanted buccal epithelium was engrafted over the urothelium through histological examination of the urethra, harvested post-transplant, which is infeasible in humans. Herein, we report the successful creation of an animal model of urethral stricture and the engraftment of epithelial cells derived from autologous buccal mucosal tissue, encapsulated in a thermo-reversible gelation polymer (TGP) scaffold, transplanted by trans-urethral route. An animal model of urethral stricture was created in Japanese white male rabbits using electro-coagulation. Buccal tissue was harvested from the rabbits and subjected to enzyme digestion, followed by 5–7 days of in vitro culture in conventional two-dimensional (2D) culture and in a 3D platform of thermo-reversible gelation polymer (3D-TGP) culture. The cells harvested from the groups were mixed and encapsulated and transplanted with TGP, by transurethral catheterization. Fourteen days later, the urethra was harvested and subjected to histological examination. The buccal biopsy tissue, cells after digestion and cells post-culture were also subjected to histological examination. Urethrogram and endoscopy images were recorded at different time points. The stricture was successfully created, with the coagulated area markedly stenosed. Histological staining of the cells after in vitro processing showed that the cells grew with native epithelial and rounded cell morphology in 3D-TGP while they differentiated into fibroblast like-cells in 2D culture. Histological staining of the urethral tissue after transplantation revealed the engraftment of the transplanted buccal mucosal cells, with stratified squamous epithelium over the specialized stratified urothelium in the urethrotomy site. We used histology to prove the successful engraftment of TGP-encapsulated buccal mucosal epithelial cells in an animal model of urethral injury with healing of the injured tissue. The model of urethral stricture and cell therapy, using a transurethral approach, recapitulates the previously reported BEES-HAUS approach and lays the foundation for larger multi-centric translational clinical studies. •An animal model of urethral stricture that closely resembles that occurring in humans could be created.•Trans-urethral transplantation of polymer scaffold encapsulated buccal mucosal epithelial cells could be accomplished.•Successful engraftment of transplanted cells onto urethrotomy site with healing, proven in this first of its kind report.